1985
DOI: 10.1007/bf01982871
|View full text |Cite
|
Sign up to set email alerts
|

Effect of benzydamine on exocytosis and respiratory burst in human neutrophils and mononuclear phagocytes

Abstract: The effect of benzydamine on stimulus-dependent respiratory burst activity and enzyme release was tested in human neutrophils, monocytes and monocyte-derived macrophages. Established anti-inflammatory compounds, indomethacin, phenylbutazone and bufexamac, were tested for comparison. Care was taken to avoid cytotoxic or cytolytic concentrations of the test compounds, and their effect on release of lactate dehydrogenase was also tested. Release of specific and azurophil granules contents were induced in human ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

1987
1987
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The most detailed study is that of Baggiolini et al who found inhibition of the oxidative burst under some conditions (Table 3) [44]. The maximal concentrations used to examine the effects ofbenzydamine on superoxide production by neutrophils was only 30 ~tmol/L; higher than those attained in plasma after oral dosage but lower than expected in oral tissues after local application and much lower than within the mouth.…”
Section: Respiratory Burst Of Neutrophils Monocytes and Macrophagesmentioning
confidence: 98%
See 2 more Smart Citations
“…The most detailed study is that of Baggiolini et al who found inhibition of the oxidative burst under some conditions (Table 3) [44]. The maximal concentrations used to examine the effects ofbenzydamine on superoxide production by neutrophils was only 30 ~tmol/L; higher than those attained in plasma after oral dosage but lower than expected in oral tissues after local application and much lower than within the mouth.…”
Section: Respiratory Burst Of Neutrophils Monocytes and Macrophagesmentioning
confidence: 98%
“…Benzydamine decreases the release of specific granules of human neutrophils stimulated with phorbol myristate acetate, PMA, or calcium ionophore, A23187, with a strong inhibition seen at 30 lxmol/L [44]. Benzydamine also inhibits azurophil granule release when neutrophils are treated with cytochalasin B and stimulated with N-formyl-methionyl-leucyl-phenylalanine, fMLP [19,44].…”
Section: Granule Releasementioning
confidence: 99%
See 1 more Smart Citation
“…4 At lower concentrations (3-30 μmol/L), this drug is also able to inhibit leukocyte-endothelial interactions, while at concentration of 10-100 μmol/L, benzydamine HCl may stabilize the mucosal membrane by virtue of its general high affinity for membranes, and may inhibit the release of azurophilic granules from neutrophils, rich in serine proteases, further contributing to its anti-inflammatory effects. 1,5 Benzydamine HCl also reduces the histamine-induced vasodilation and vascular permeability. 6 Benzydamine HCl shows antithrombotic activity 7 and the inhibition of the collagen-induced aggregation appears to be rather selective vs. other NSAIDs.…”
Section: The Mechanisms Of Action Of Benzydamine Hclmentioning
confidence: 99%